The Effect of The Inquiry Method on Improving the Understanding of News Text in Junior High School - Muhammad Dani Setia Nurilahi; Ika Mustika (IKIP Siliwangi, 2022)
The purpose of this study is to empirically demonstrate the effectiveness of the research method in improving the understanding of news texts among students. The research method was carried out using an experimental method comparing the learning of class VIIIA students with the survey method as experimental learning with students in class VIIIB who studied using the lecture method as the control class. The survey was conducted in 2021/2022 at SMP Bina Negara1 Arjasari. Sampling was carried out using a targeted sampling technique. The sample of this study consisted of 60 students with the same curriculum background who did not have a particular cluster or had the same average score. The term evaluation test in the form of an essay test serves as a research tool. Methods of data analysis using tests. Based on the calculation results obtained tcount = 9.39 and ttable = 2.001 with a significance level of 5%. This means that the value of tcount > ttable. These results indicate that H0 is rejected and H1is accepted. Acceptance of H1 means that the hypothesis that the provision of research methods affects students' understanding of the message text has been proven. ABSTRAK Tujuan penelitian ini adalah untuk menunjukkan secara empiris efektivitas metode penelitian dalam meningkatkan pemahaman teks berita di kalangan mahasiswa. Metode penelitian dilakukan dengan menggunakan metode eksperimen membandingkan pembelajaran siswa kelas VIIIA dengan metode survey sebagai pembelajaran eksperimen dengan siswa di kelas VIIIB yang pembelajarannya dengan metode ceramah sebagai kelas kontrol. Survei dilakukan pada tahun 2021/202 di SMP Bina Negara1 Arjasari Kabupaten Bandung. Pengambilan sampel dilakukan dengan menggunakan teknik sampling bertarget. Sampel penelitian ini terdiri dari 60 siswa dengan latar belakang kurikulum yang sama yang tidak memiliki klaster tertentuatau memiliki nilai rata-rata yang sama. Istilah tes evaluasi dalam bentuk tes esai berfungsi sebagai alat penelitian. Metode analisis data menggunakan tes. Berdasarkan hasil perhitungan diperoleh thitung = 9,39 dan ttabel = 2,001 dengan taraf signifikansi 5%. Artinya nilai thitung > ttabel. Hasil ini menunjukkan bahwa H0 ditolak dan H1 diterima. Penerimaan H1 berarti hipotesis bahwa pemberian metode penelitian berpengaruh terhadap pemahaman siswa terhadap teks pesan telah terbukti.